Adult accompaniment and the risk of pedestrian injury on the school-home journey. Issue 4 (December 1995) - Roberts, I.
Abstract : STUDY OBJECTIVE: To quantify the effect of adult accompaniment on the risk of pedestrian injury on the school-home journey. DESIGN: A community based case-control study. SETTING: The Auckland region of New Zealand. PARTICIPANTS: Cases (n = 54) were all children killed or hospitalized as a result of a pedestrian injury occurring on the school-home journey between 1 January 1992 and 1 March 1994. The response rate for the case group was 98%. Controls (n = 157) were a random sample of all children who walk to and from school in the study region. The response rate for the control group was 100%. MAIN RESULTS: Adult accompaniment on the school-home journey was associated with a reduced risk of injury (odds ratio (OR) 0.36, 95% confidence interval (CI) 0.04 to 1.66). This effect persisted after controlling for age, sex, and socioeconomic status (OR 0.31, 95% CI 0.07 to 1.49). CONCLUSIONS: Adult accompaniment on the school-home journey may have the potential to significantly reduce child pedestrian injury rates. The effect of adult accompaniment may have important implications for the interpretation of child pedestrian exposure studies.